Optimasi Pendistribusian Air PDAM Payakumbuh dengan VAM dan Pengujian Optimalitasnya Menggunakan Metode MODI - Annisya Annisya; Hendra Syarifuddin; Riry Sriningsih (Journal of Mathematics UNP, 2021)
Abstract – Optimization model is one of the analysis models which identictooperations research. Transportation model relatesto the determination of the least cost plan to send an item from a number of source to a number of destination areas, like VAM. VAM principle ischooseleastof the least cost of eachrowandcolumnand thencalculate the differencebetweenit. Thedifferenceis called Vogel number. VAMmethodswillprovidesan initial solution to findthe nearest  optimalsolution. Thereforeitis necessary to do a testthe optimalityoftheinitial solutionusingMODI. MODI method is to resolve the  case of the transportation that was developed from the stepping stone method. The purpose of this  research is determining the optimal water distribution with minimum distribution cost. The result ofthis indicate that the operating costs is Rp. 6,344,697.13 before it was done minimization and the operational costsis Rp. 5,284,908.08 after it was done minimization by VAM. Keywords – vogel approximation, modified distribution, optimization, water distribution.